GENDER BIAS IN ENGLISH TEXTBOOK FOR THE TWELFTH GRADE STUDENTS - Ester Kristina Sibarani; Willem Saragih (Universitas Negeri Medan, 2023)
This study aims to describe how gender bias is represented in the English textbook for the twelfth-grade students. This study was conducted by using descriptive qualitative research. The subject of this study was English textbook entitled “Bahasa Inggris” used in twelfth grade students. The study used content analysis technique. The data were collected from texts and pictures. In total, there were 100 pictures and 269 texts that consisted of gender to be analyzed through six categories of gender bias which are proposed by Porreca in 1984. The findings of the study showed that female and male omission, female was leading by 51% to 49%. Female and male firstness, male was leading by 87% to 13%. Female and male occupational role, male was leading by 59% to 41%. Female and male noun, female was leading by 74% to 26%. The textbook has one kind of masculine generic structure. Female and male adjective, female was leading by 63% to 37%. The findings revealed that gender bias still exists in the textbook. The textbook does not portray a gender- balanced portrayal of male and female. Females are still portrayed as doing more housework like baking, decorating the room, and caring for children. However, based on the number of occupations, males are portrayed as dominant in doing social occupations.